Chlamydia Pneumoniae CdsL Regulates CdsN ATPase Activity, and Disruption with a Peptide Mimetic Prevents Bacterial Invasion - Stone, Chris B.; Bulir, David C.; Emdin, Connor A.; Pirie, Ryan M.; Porfilio, Elisa A.; Slootstra, Jerry W.; Mahony, James B. (Frontiers in Microbiology, 2011)
Chlamydiae are obligate intracellular pathogens that likely require type III secretion (T3S) to invade cells and replicate intracellulary within a cytoplasmic vacuole called an inclusion body. C. pneumoniae possess a YscL ortholog, CdsL, that has been shown to interact with the T3S ATPase (CdsN). In this report we demonstrate that CdsL down-regulates CdsN enzymatic activity in a dose-dependent manner. Using PepScan epitope mapping we identified two separate binding domains to which CdsL binds viz. CdsN 221-229 and CdsN265-270. We confirmed the binding domains using a pull-down assay and showed that GST-CdsN221-270, which encompasses these peptides, co-purified with His-CdsL. Next, we used orthology modeling based on the crystal structure of a T3S ATPase ortholog from E. coli, EscN, to map the binding domains on the predicted three dimensional structure of CdsN. The CdsL binding domains mapped to the catalytic domain of the ATPase, one in the central channel of the ATPase hexamer and one on the outer face. Since peptide mimetics have been used to disrupt essential protein interactions of the chlamydial T3S system and inhibit T3S-mediated invasion of HeLa cells, we hypothesized that if CdsL – CdsN binding is essential for regulating T3S then a CdsN peptide mimetic could be used to potentially block T3S and Chlamydial invasion. Treatment of EBs with a CdsN peptide mimetic inhibited C. pneumoniae invasion into HeLa cells in a dose-dependent fashion. This report represents the first use of Pepscan technology to identify binding domains for specific T3S proteins viz. CdsL on the ATPase, CdsN, and demonstrates that peptide mimetics can be used as anti-virulence factors to block bacterial invasion.